2019
DOI: 10.3390/su11051370
|View full text |Cite
|
Sign up to set email alerts
|

Are Renewables as Friendly to Humans as to the Environment?: A Social Life Cycle Assessment of Renewable Electricity

Abstract: The adoption of renewable energy technologies in developing nations is recognized to have positive environmental impacts; however, what are their effects on the electricity supply chain workers? This article provides a quantitative analysis on this question through a relatively new framework called social life cycle assessment, taking Malaysia as a case example. Impact assessments by the authors show that electricity from renewables has greater adverse impacts on supply chain workers than the conventional elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…There is however also the possibility that water use will be increased due to growth of renewables, that can however impact public acceptance of renewables [ 50 ]. Some studies argue that renewables are not as friendly to humans as to the environment but that they also have less impact per dollar-spent [ 51 ], so all of these can change priorities and acceptance of specific renewables in the future. The general public also favors renewable energy sources which can be identified as more expensive but of course environmentally more sound.…”
Section: Discussionmentioning
confidence: 99%
“…There is however also the possibility that water use will be increased due to growth of renewables, that can however impact public acceptance of renewables [ 50 ]. Some studies argue that renewables are not as friendly to humans as to the environment but that they also have less impact per dollar-spent [ 51 ], so all of these can change priorities and acceptance of specific renewables in the future. The general public also favors renewable energy sources which can be identified as more expensive but of course environmentally more sound.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a Fully Modified Ordinary Least Square (FMOLS) regression model analysis, Singh et al [26] argue that renewable energy production is associated with a positive and statistically significant impact on economic growth in both developed and developing countries for the period 1995-2016. Starting with the analysis based on a Malaysian Case Study, Takeda et al [27] showed that electricity from renewables has greater adverse impact on workers from the supply chain than the conventional electricity mix, in view of the social aspects countered.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Employees who are involved in sustainable activities and adopt sustainable development principles become sustainable human resources [37,38]. The challenge is how to apply new technologies, acquire new e-skills, and combine them with communication channels [39,40].…”
Section: Conceptual Frameworkmentioning
confidence: 99%